Rancang Bangun Konstruksi Mesin Pencacah Plastik Multifungsi Kapasitas 50 Kg/Jam - Elvis Adril; Fardinal Fardinal; Yuliarman Yuliarman; Nasirwan Nasirwan; Vemil Beswara (Politeknik Negeri Padang, 2023)
The use of plastic in human life is increasing. In an effort to utilize plastic waste as a recycled material, it is necessary to create a tool or machine that can be operated as a tool for chopping plastic. The main components of a plastic chopping machine are the electric motor, pulleys and belts, blades and shafts, pins, bearings, hoppers and frames. The working principle of the plastic chopping machine is that the electric motor shaft rotates then transmits power to the chopping knife shaft with the help of pulleys and v-belts to chop the plastic that enters from the hopper. The plastic chopping machine uses power from a 1.5 HP electric motor with a motor speed of 1450 rpm and a shaft rotation speed of 580 rpm. The angle iron used for construction planning is SS4400 steel angle iron with a yield strength of 245 N/mm2, a safety factor of 5, and the bending stress is smaller than the allowable stress so that it is safe to use as a frame construction for plastic chopping machines.